2016
DOI: 10.1111/1440-1681.12665
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein 6—a possible new player in pathophysiology of heart failure

Abstract: Derangement of bone morphogenetic protein (BMP) signalling was observed in cardiovascular disorders. The present study assesses the diagnostic and prognostic value of BMP6 plasma concentration in chronic heart failure (CHF). 130 CHF patients and 32 controls participated in the study. BMP6 plasma level was measured at baseline. During 12-month follow-up death and hospitalisation with CHF exacerbation were recorded. BMP6 was significantly increased in CHF patients with highest concentration in most advanced dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…59 Recent observations of increased BMP6 levels in HF are in concert with these finding, and they suggest a reactive response to cardiac injury. 60 In conclusion, the release of hepcidin and BMP6 during cardiac injury might serve as part of an orchestrated cardiac response to protect the myocardial function. Still, molecular mediators of BMP6 expression in the heart are unknown, whereas the relation of BMP6 with cardiac hepcidin remains to be elucidated.…”
Section: Cardiac Stress Is Regularly Associated With Increased Hepcidmentioning
confidence: 97%
“…59 Recent observations of increased BMP6 levels in HF are in concert with these finding, and they suggest a reactive response to cardiac injury. 60 In conclusion, the release of hepcidin and BMP6 during cardiac injury might serve as part of an orchestrated cardiac response to protect the myocardial function. Still, molecular mediators of BMP6 expression in the heart are unknown, whereas the relation of BMP6 with cardiac hepcidin remains to be elucidated.…”
Section: Cardiac Stress Is Regularly Associated With Increased Hepcidmentioning
confidence: 97%
“…BMP6 is expressed in developing hearts and mice with combined BMP6 and BMP7 loss exhibit a delay in formation of the outflow tract endocardial cushions (127). Although a clinical study showed increased circulating levels of BMP6 in patients with advanced heart failure (128), information on the regulation and role of BMP6 in the infarcted myocardium is lacking.…”
Section: The Bmp/gdf Subfamilymentioning
confidence: 99%
“…BMP2 has been found to alleviate heart failure with type 2 diabetes by inhibiting inflammasome formation ( 27 ), and is inversely correlated with the concentrations of atrial natriuretic peptide and brain natriuretic peptide in chronic heart failure patients with diabetes. Another study observed increased BMP6 in chronic heart failure patients, suggesting that BMP6 may be involved in the pathophysiology of systolic heart failure ( 28 ). In addition, SMAD1 protein was differentially expressed in a high-salt diet-induced HFpEF model ( 29 ).…”
Section: Discussionmentioning
confidence: 99%